Peran Attachment terhadap Kepuasan Penikahan - Kezia Laraesa; Ellen Theresia (Universitas Kristen Maranatha, 2022)
The divorce rate in Bandung has been increasing each year, may indicate marital satisfaction problem. This research was conducted to obtain contribution adult attachment style to marital satisfaction among young adults in Bandung. Data were collected from 386 respondents in Bandung. The measuring instrument used was Trent Relationship Scales Questionnaire and ENRICH Marital Satisfaction Scale (EMS). This research analyzes using simple linear regression in the SPSS 25 program, showed that all of the adult attachment style has significant simultaneous contribution to marital satisfaction (Sig. 0.000-0.022>0.05). Secure attachment contributed 1.6%, preoccupied attachment contributed 1.4%, dismissing attachment contributed 5% and fearful attachment contributed the most to marital satisfaction with a contribution of 9.8%. The conclusion is, all the adult attachment style has a significant contribution to marital satisfaction, mainly fearful attachment. Further research can be carried out to examine economic status or age of marriage as other factors that influence marital satisfaction.